Suicide Attempts Among French and Brazilian Adolescents Admitted to an Emergency Room. A Comparative Study of Risk and Protective Factors - Rufino, Natalia C.; Mirkovic, Bojan; Consoli, Angèle; Pellerin, Hugues; Santos, Juliana P. M.; Fidalgo, Thiago M.; Gerardin, Priscille; Silveira, Dartiu X.; Cohen, David (Frontiers in Psychiatry, 2020)
Background: Suicide is the second most common cause of preventable mortality among Brazilian and French adolescents. The aim of the current study was to compare the main risk and protective factors associated with a suicide attempt (SA) and to highlight differences based on geographical characteristics. Method: We compared a Brazilian sample (N= 45) of adolescents admitted to the emergency room of a public hospital in Sao Paulo for SA to a French sample (N= 320) of adolescents hospitalized for SA across 5 paediatric departments. Then, we ran several multivariate models to examine how each selected variable was related to geographic origin and to the other selected variables linked to geographic origin. Results: The two samples presented no significant differences regarding gender, age or schooling. Both samples had high rates of depressive disorders, anxiety disorders, substance use, disruptive disorders, borderline psychopathology and lifetime SAs. However, the Brazilian sample presented significantly higher levels of psychopathology and had more insecure attachment relationships (fearful and detached), whereas the French sample had a more secure attachment style. Brazilian adolescents had more recourse to spiritual beliefs and spiritual support, whereas the French adolescents had higher scores on the Reasons for Living Inventory and used more help-seeking strategies from their social network, mainly close friends. Multivariate models showed that two productive coping strategies (seeking spiritual support and social action) and the dependence score were significantly associated with membership in the Brazilian cohort, whereas a secure attachment style and depression severity (evaluated by the Beck Depression Inventory) were significantly associated with membership in the French cohort. Conclusion: Despite presenting similar psychopathologies, Brazilian adolescents presented a more insecure attachment style and used the religious kind of coping more commonly than their French counterparts. We hypothesize that religion may compensate for the social vulnerabilities present in a middle-income country such as Brazil. More transcultural studies may help to elucidate this phenomenon.